Analysis of prejudice and discrimination by healthcare professionals against lesbian users in Basic Health Units (Research, Society and Development, 2023)
The aim was to investigate and analyze the prejudice of doctors, nurses, nursing technicians, and community health agents who work in Basic Health Units (BHUs) against lesbian users. For this purpose, an exploratory and descriptive study was conducted, of a cross-sectional nature, with a qualitative design and non-probabilistic sampling, carried out in different Basic Health Units distributed among the five sanitary districts of the city of João Pessoa, Paraíba, Brazil. The study included 31 healthcare professionals who, at the time of data collection, were working in one of the visited BHUs. Data collection utilized a sociodemographic questionnaire and the Priming technique, with subsequent questions following the stimulus. As a result, it was observed that the disregard, by healthcare professionals, of the existence of situations of discrimination in healthcare services, indicated the possibility of reinforcing the positive social identity of the group. By denying the occurrence of discrimination in the services where they work, participants demonstrated a potential transformation in the quality of care, avoiding possible social judgments. There were also indications of subtle prejudice on the part of participants, as they attempted to justify the denial of healthcare rights to lesbian users, potentially trying to suppress their own prejudices towards these users. Finally, it was concluded that the obtained data can serve as indicators for managers regarding how healthcare professionals perceive the sexual health of lesbian women, guiding the development of alternatives that promote reflection and changes in professional conduct.